KEANEKARAGAMAN JENIS SERANGGA DI HUTAN TINJOMOYO KOTA SEMARANG, JAWA TENGAH - Niken Subekti (Tengkawang : Jurnal Ilmu Kehutanan, 2012)
As a part of biodiversity, insects should be conserved. Some insects are beneficial for human life. Ecologically, insects maintain the ecosystem balance and enrich natural resources. Tinjomoyo Forest in Semarang Municipality plays a role as the ecotourism area. The aim of the study was to understand the diversity of the insects of Tinjomoyo Forest, Semarang. A transect method has been employed with the transect dimensions of 20 x 20 m, 10 x 10 m, and 5 x 5 m, with three replicates. The insect identification was carried out in the Biology Laboratory, UNNES. Result showed that 19 insects live in Tinjomoyo Forest with the diversity index of 0.04 to 1.20, and this is considered low. Oechopylla smaragdina has the highest Importance Value Index of 11.89%, whereas Tincola bisselliella has the lowest Importance Value Index of 3.18%. Several factors influence the insect diversity, such as the distribution, the habitat selection, the environmental condition, the vegetation, and the food availability. Keywords: Diversity, insect, species, Tinjomoyo